The representation of the Trimurti concept in the architecture of Padma Tiga at Pura Luhur Muncaksari (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Padmasana architecture is the most important sacred building in Balinese temples. Padmasana functions as the sthana (seat) of God and has many types, depending on the concept of God being represented. The ‘three padmas’ form, one of the types of padmasana architecture found in the Luhur Muncaksari Temple, is very different from the padmasana forms found in other major temples in Bali. This uniqueness often causes difficulties in understanding its function and symbolic meaning, both for the general public and intellectual circles. To understand its representation, an interpretation is carried out by broadening the horizon of understanding, from the parts of the form to the form as a whole. The purpose of this study is to discover the concept of God represented in the visual form of the ‘three padmas’. The findings reveal that the padma tiga at Pura Luhur Muncaksari symbolically represents the Trimurti: Brahma, Vishnu, and Shiva, through its spatial composition, structural elements, and ornamental features. These findings are crucial for informing the development and preservation of traditional Balinese architecture, which is rooted in cosmological and philosophical foundations.
Keywords: Padma Tiga; Pura Luhur Muncak Sari; Representation; Trimurti concept